2012
DOI: 10.4049/jimmunol.1200634
|View full text |Cite
|
Sign up to set email alerts
|

Type I Alveolar Epithelial Cells Mount Innate Immune Responses during Pneumococcal Pneumonia

Abstract: Pneumonia results from bacteria in the alveoli. The alveolar epithelium consists of type II cells, which secrete surfactant and associated proteins, and type I cells, which constitute 95% of the surface area and met anatomic and structural needs. Other than constitutively expressed surfactant proteins, it is unknown whether alveolar epithelial cells have distinct roles in innate immunity. Since innate immunity gene induction depends on NF-κB RelA (also known as p65) during pneumonia, we generated a murine mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
101
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(104 citation statements)
references
References 54 publications
3
101
0
Order By: Relevance
“…Platelets and endothelial and epithelial cells can secrete CXCL5 (31,39,41). Our experiments revealed that upon in vitro M. tuberculosis infection, only AECII produced CXCL5, while CXCL2 was secreted by PMNs and BMDMs, and CXCL1 was secreted by BMDMs and AECII.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Platelets and endothelial and epithelial cells can secrete CXCL5 (31,39,41). Our experiments revealed that upon in vitro M. tuberculosis infection, only AECII produced CXCL5, while CXCL2 was secreted by PMNs and BMDMs, and CXCL1 was secreted by BMDMs and AECII.…”
Section: Discussionmentioning
confidence: 77%
“…Experiments with BM chimeric mice and MACS-sorted lung cells confirmed and extended our in vitro and in situ findings that CXCL5-dependent PMN recruitment was exclusively driven by radioresistant lung-resident cells and not by radiosensitive hematopoietic cells. CXCL5 expression is neither cell type nor organ specific but, rather, is expressed by diverse tissue-resident cells, including car- diac myocytes (57), alveolar epithelial cells (31,41), enterocytes (38), aortic endothelial cells (58), and kidney tubular cells (E. Disteldorf and C. Krebs et al, unpublished observations). This broad expression emphasizes the general role of CXCL5-secreting resident tissue cells in orchestrating PMNs in response to microbial and inflammatory danger signals (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lavage fluid was centrifuged at 300 g for 5 minutes at 4°C, and cell pellets were used for differential counts. BALF cell counts were performed as previously described (39), with cytocentrifuged slides stained with the Diff-Quik staining kit (Dade Behring) after counting of suspended cells using a hemocytometer. For BALF cytokine measurement, the supernatant of the first 1-ml lavage sample was saved separately at -80°C for protein analysis by ELISA (R&D Systems).…”
Section: Methodsmentioning
confidence: 99%
“…The first step in regenerative medicine for end-stage lung diseases is generation of alveolar epithelium containing two cell types: alveolar epithelial type I and type II cells (AEC I and II). AEC I cells are large, flattened cells that make up 95% of the alveolar lining area and are responsible for gas exchange, whereas AEC II cells are cuboidal cells, more abundant but smaller than AEC I cells, that make up 5% of the alveolar lining area [1,2]. AEC I cells are terminally differentiated, unable to replicate, and susceptible to environmental toxicants and pathogens.…”
Section: Introductionmentioning
confidence: 99%